PERANCANGAN APLIKASI UMSTATIKA BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN PADA MATERI STATIKA TERTENTU - Ade Putra Irawan; Chendra Amigo; Ryan Evian Susandy; Suci Lestari; Helga Yermadona; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The purpose of this study is to create and implement effective learning media to facilitate lecturers and students in conducting learning in the Civil Engineering Study Program, Faculty of Engineering, Muhammadiyah University, West Sumatera, namely designing Umstatika learning applications by designing using use case diagrams, making the system in accordance with the design that has been made and implement the system that has been created and perform testing on the system. In collecting data, researchers used the method of observation, interviews and literature study. Meanwhile, in developing the system, researchers use the type of Research and Development (R&D) research referring to the waterfall model. Applications made using Android Studio, Figma. Applications that have been made are tested using the black box testing method. This research produces an “Umstatika App” learning application that helps the faculty in carrying out the learning process during lectures and also helps students to make it easier to learn certain basic statics materials anywhere and anytime. Keywords: Aplikasi Mobile, Umstatika, android studio, figma, waterfall.